Cleavage via Selective Catalytic Oxidation of Lignin or Lignin Model Compounds into Functional Chemicals - Xiu-Zhi Wei; Jianguo Liu; Longlong Ma (ChemEngineering, 2021)
Lignin, a complex aromatic polymer with different types of methoxylated phenylpropanoid connections, enables the sustainable supply of value-added chemicals and biofuels through its use as a feedstock. Despite the development of numerous methodologies that upgrade lignin to high-value chemicals such as drugs and organic synthesis intermediates, the variety of valuable products obtained from lignin is still very limited, mainly delivering hydrocarbons and oxygenates. Using selective oxidation and activation cleavage of lignin, we can obtain value-added aromatics, including phenols, aldehydes, ketones, and carboxylic acid. However, biorefineries will demand a broad spectrum of fine chemicals in the future, not just simple chemicals like aldehydes and ketones containing simple C = O groups. In particular, most n-containing aromatics, which have found important applications in materials science, agro-chemistry, and medicinal chemistry, such as amide, aniline, and nitrogen heterocyclic compounds, are obtained through n-containing reagents mediating the oxidation cleavage in lignin. This tutorial review provides updates on recent advances in different classes of chemicals from the catalytic oxidation system in lignin depolymerization, which also introduces those functionalized products through a conventional synthesis method. A comparison with traditional synthetic strategies reveals the feasibility of the lignin model and real lignin utilization. Promising applications of functionalized compounds in synthetic transformation, drugs, dyes, and textiles are also discussed.